(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Considering the history of the theater of the Brazilian Northeast, in the terms in which Paschoal Carlos Magno will recognize the poetics introduced by the Teatro do Estudante de Pernambuco in the 1940s, this article sheds light on the encounters that the theatrical movement from Recife established with the stages of Rio de Janeiro, considered the center of the country’s theatrical culture. In particular, it is interesting here to highlight the specificities of the participation of the Auto da Compadecida in the first edition of the Festival de Amadores Nacionais in 1957 for the context of affirming the visibility strategies that marked the Northeast as a place in Brazilian theater.